Genotyping of the genus Proteus by rpoB sequence analysis (Italian Journal of Public Health, 2005)
Background. The genetic relationship among different species within the genus Proteus has still not beenclarified and previous studies by rRNA gene restriction patterns (ribotypes) suggested a high geneticvariability in the presently recognised nomenspecies.Methods. The usefulness of rpoB sequencing for inter- and intraspecies discrimination in the genus Proteuswas evaluated on 11 type and clinical strains belonging to the four described species: P. penneri, P. vulgaris,P. mirabilis, and P. myxofaciens.Results. The rpoB sequencing proved able to characterise the different species, showing six well definedrpoB sequence groups in the 1153 bp region analysed. P. myxofaciens and P. mirabilis could be clearlydifferentiated from the types and clinical strains of the other species showing sequence divergences of 19.5-23% and 6.6-7.6%, respectively. Two groups of P. vulgaris sequences could be described, one of themincluding the new strain type, differing from each other by 3.3-3.6% of their nucleotides (nt) and for both ofthem 6.5-6.8% nt differences from the stand-alone former P. vulgaris strain type were found. P. penneridiffered by only 2.3-3% from all P. vulgaris strains, however, differed from the former P. vulgaris strain typeby 5.5-5.8%.Conclusions. Our results confirm previous ribotyping data regarding the validity of the presently recognisednomenspecies within the genus Proteus, but provides further evidence for the existence of geneticdifferences within the P. vulgaris species.
Keywords: Proteus; genetic analysis; rpoB sequencing; ribotyping